Evaluasi Tata Fasilitas Publik di Objek Wisata Candidasa Kabupaten Karengasem - Astiti, Ni Luh Seri; Sugianthara, Anak Agung Gede; Dharmadiatmika, I Made Agus (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023, 2023)
Evaluation of Public Facilities at the Candidasa Tourism Object, Karangasem Regency . Karangasem is one of the regencies in Bali Province which located on the eastern side of Bali Island. Candidasa as one of the strategic tourism areas is one of the alternative tourism objects in Karangasem Regency. Candidasa has various facilities that can be used by visitors as a place for vacation and recreation. Those facilities are still not in accordance with the standard and improper placement. This study aims to maximize the existing facilities by giving the recommendation which referred to standard facilities placement. The research method used is a survey method with observation techniques, interviews, documentation, questionnaires, and literature study. The results showed that there were several facilities that had not followed the standardization and improper placement. Facilities available at Candidasa Tourism Objects are: rubbish bin, toilets, culinary place, gazebos, jogging tracks, parking and recreational facilities in the form of swings from trees. Many visitor activities are carried out in the Lotus Lagoon area, Candidasa Beach Rest Area, Batu Madeg Market Area and Areas along the Candidasa Tourism Object Street, but some of the facilities provided are in poor condition. The efforts made to improve quality are by following the applicable standards and guidelines.